2016
DOI: 10.1038/nature19797
|View full text |Cite|
|
Sign up to set email alerts
|

Upward revision of global fossil fuel methane emissions based on isotope database

Abstract: Methane has the second-largest global radiative forcing impact of anthropogenic greenhouse gases after carbon dioxide, but our understanding of the global atmospheric methane budget is incomplete. The global fossil fuel industry (production and usage of natural gas, oil and coal) is thought to contribute 15 to 22 per cent of methane emissions to the total atmospheric methane budget. However, questions remain regarding methane emission trends as a result of fossil fuel industrial activity and the contribution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
482
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 458 publications
(535 citation statements)
references
References 19 publications
29
482
3
Order By: Relevance
“…Whereas the decreasing trend in δ 13 C in CH 4 suggests a significant, if not dominant, contribution from increasing emissions by microbial CH 4 sources (Schaefer et al, 2016;Nisbet et al, 2014), concurrent ethane and methane column measurements suggest a significant role (likely at least 39 %) for oil and gas production (Hausmann et al, 2016), which could be consistent when assuming a concomitant decrease in biomass burning emissions (heavy source for 13 C), as suggested by the GFED database (Giglio et al, 2013). Yet accounting for the uncertainties in the isotopic signatures of the sources and their trends may suggest different portionings of the global methane sources between fossil fuel and biogenic methane emissions (Schwietzke et al, 2016). A possible positive OH trend has occurred since the 1970s followed by stagnation to decreasing OH in the 2000s, possibly contributing significantly to recent observed atmospheric methane changes (Dalsøren et al, 2016;Rigby et al, 2008;McNorton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the decreasing trend in δ 13 C in CH 4 suggests a significant, if not dominant, contribution from increasing emissions by microbial CH 4 sources (Schaefer et al, 2016;Nisbet et al, 2014), concurrent ethane and methane column measurements suggest a significant role (likely at least 39 %) for oil and gas production (Hausmann et al, 2016), which could be consistent when assuming a concomitant decrease in biomass burning emissions (heavy source for 13 C), as suggested by the GFED database (Giglio et al, 2013). Yet accounting for the uncertainties in the isotopic signatures of the sources and their trends may suggest different portionings of the global methane sources between fossil fuel and biogenic methane emissions (Schwietzke et al, 2016). A possible positive OH trend has occurred since the 1970s followed by stagnation to decreasing OH in the 2000s, possibly contributing significantly to recent observed atmospheric methane changes (Dalsøren et al, 2016;Rigby et al, 2008;McNorton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that assignment of representative isotopic signatures of various CH 4 sources remains uncertain due to their large spatial and temporal variability across the globe (e.g. Sherwood et al, 2017), which could result in large uncertainties of isotope-based estimates of the global CH 4 budget (Schwietzke et al, 2016). Nonetheless, the value of isotope measurements was amply demonstrated by recent studies which suggested shifts in the global CH 4 source over the last decades (Schaefer et al, 2016;Rice et al, 2016;Nisbet et al, 2016;Schwietzke et al, 2016); without isotopic analyses such conclusions would have been difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating δ 13 C-CH 4 and δD-CH 4 data sets in chemistry transport models is useful for quantitatively separating different CH 4 source categories and attempts have been made to reduce uncertainties in the global CH 4 budget (e.g. Hein et al, 1997;Mikaloff Fletcher et al, 2004a, b;Monteil et al, 2011;Kirschke et al, 2013;Ghosh et al, 2015;Rice et al, 2016;Schaefer et al, 2016;Schwietzke et al, 2016;Röckmann et al, 2016;Turner et al, 2017;Rigby et al, 2017). However, although an increasing number of δ 13 C-CH 4 and δD-CH 4 data have been reported over the last decades, significant measurement offsets among laboratories have been found for both δ 13 C-CH 4 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A threestep methodology was applied. First, gridded input files of the natural methane emission sources and soil sink were built 30 using published inventories and flux information (Ciais et al, 2013;Dutaur and Verchot, 2007;EPA, 2010;Etiope et al, 2008;Fung et al, 1991;Kirschke et al, 2013;Melton et al, 2013;Saunois et al, 2016;Schwietzke et al, 2016 emissions for all other emission sources of short-lived air pollutants. ModelE2-YIBs is described in Sect.…”
Section: Interactive Methane In Modele2-yibsmentioning
confidence: 99%
“…A spatially explicit methane emissions inventory is necessary for running interactive climate simulations that apply dynamic methane emissions. In this study, published sector-specific data on natural methane fluxes (Ciais et al, 2013;Dutaur and Verchot, 2007;EPA, 2010;Etiope et al, 2008;Fung et al, 1991;Kirschke et al, 2013;Melton et al, 2013;Saunois et al, 2016;Schwietzke et al, 2016) are used in conjunction with atmospheric modeling and atmospheric methane observations (Dlugokencky et al, 2015) to 20 guide development of a spatially explicit contemporary budget of natural methane emissions and the methane soil sink. The NASA ModelE2-Yale Interactive terrestrial Biosphere (ModelE2-YIBs) global chemistry-climate model (Schmidt et al, 2014;Yue and Unger, 2015) is subsequently used to run an interactive methane simulation representative of year 2005 that applies the refined natural methane flux inventory.…”
Section: Introductionmentioning
confidence: 99%